Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I know to use Wilson's Theorem and that each element in the second half is congruent to the negative of the first half, but I'm not sure how to construct a proof for it.

share|cite|improve this question
I edited your title because it is extremely likely you did not really mean $P-12$. – Erick Wong Oct 28 '12 at 0:35
For any p in the form 4k+3, ((p-1)/2)! is congruent to -1 mod p or 1 mod p – Amanda Oct 28 '12 at 0:36
@Amanda did you mean $(p-12)!$ or $((p-1)/2)!$? – user17762 Oct 28 '12 at 0:37
((p-1)/2)! Sorry! – Amanda Oct 28 '12 at 0:40
A hint: write $p = 4k + 3$ and prove that $((2k + 1)!)^2 = + 1$ – Jonah Sinick Oct 28 '12 at 0:46

$p-r\equiv -r\pmod p\implies r\equiv-(p-r)$

For uniqueness, $r\le p-r$ or $2r\le p\implies r\le\frac p 2$

So, $1\le r\le \frac{p-1}2$ as $p$ is odd

Putting $r=1,2,3,\cdots,\frac{p-3}2,\frac{p-1}2$ we get,






So, there are $\frac{p-1}2$ pairs so,


Using Wilson's theorem, $(-1)^{\frac{p-1}2}\left((\frac{p-1}2)!\right)^2\equiv-1\pmod p$

If $p\equiv3\pmod 4,p=4t+3$ for some integer $t$,

So, $\frac{p-1}2=2t+1$ which is odd, so $(-1)^{\frac{p-1}2}=-1$

$\implies \left((\frac{p-1}2)!\right)^2\equiv1\pmod p$

$\implies \left(\frac{p-1}2 \right)!\equiv\pm1\pmod p$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.